Πλαίσιο στοχαστικής προσομοίωσης σε ψευδο-συνεχή χρόνο για την εκτίμηση πλημμυρικών παροχών - Μουστάκης, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Υδατικών Πόρων και Περιβάλλοντος, 2017)
Typically, flood modelling in the context of everyday engineering practices is addressed through event-based deterministic tools, e.g., the well-known SCS-CN method. A major shortcoming of such approaches is the ignorance of uncertainty, which is associated with the variability of soil moisture conditions and the variability of rainfall during the storm event.